Tindak Pidana Korupsi dalam Persepektif Hukum Positif dan Hukum Islam - Mustakid, Dodo (Edulaw : Journal of Islamic Law and Yurisprudance, 2021)
Corruption is a crime that not only damages State finances but also damages the joints of national and state life. Therefore the application of Article 2 of Law no. 20 of 2001 against perpetrators of criminal acts of corruption for state officials in the perspective of Islamic law can be implemented because it is appropriate and in line with maqasid al-tasyri 'in the sense that it still considers the public interest which is benefit-oriented and rejects all evil. Corruption is against the objectives of law (maqasid al-tasyri ') in order to protect religion, life, property, descent and reason. Because it is in accordance with applicable justice and if proven guilty, the perpetrator of corruption and proven guilty can be subject to maximum punishment. The main problems presented by the compilers in the discussion of corporate crime in the perspective of Islamic law and positive law are: 1) What is the positive legal view of corruption? and what are the sanctions for the perpetrators of corruption in positive law? 2) What is the view of Islamic law on corruption? And how to sanction corruption in Islamic law? The research method used is a comparative descriptive qualitative research method which is sourced from various references both classical books and comprehensive books as the main reference, namely by presenting a comparative depiction of the problem of corruption (comparison) according to versions of positive law and Islamic law. . with the aim of obtaining relevant and credible answers so that readers or knowledge seekers can draw conclusions about the problem of corruption appropriately. From the description of the description of the criminal act of corruption above, it can be concluded that, in terms of Islamic religion, criminal acts are the prohibitions of syara 'which are threatened by Allah with the punishment of had or ta'zir. Meanwhile, according to positive law, a criminal act is an act that violates the prohibitions regulated by the rule of law which is punishable by criminal sanctions. Criminal acts in Islam will receive appropriate sanctions, such as murder must be punished by death. Meanwhile, according to positive law, offenders of a crime are punished with conditional provisions, such as someone who kills is sentenced to only a few years in prison, which should be a death sentence, on the grounds of compassion or protecting human rights. Abstrak Korupsi merupakan kejahatan yang bukan saja hanya merusak keuangan Negara tetapi juga merusak sendi-sendi kehidupan berbangsa dan bernegara. Karena itu penerapan pasal 2 Undang-undang No. 20 tahun 2001 terhadap pelaku tindak pidana korupsi bagi penyelenggara negara dalam prespektif hukum Islam bisa dilaksanakan karena sesuai dan sejalan dengan maqasid al-tasyri’ dalam artian tetap mempertimbangkan kepentingan umum yang berorientasi pada kemaslahatan dan menolak segala kemungkaran. Korupsi bertentangan dengan tujuan hukum (maqasid al-tasyri’) dalam rangka menjaga agama, jiwa, harta, keturunan, dan akal. Oleh karena sesuai dengan keadilan yang berlaku dan bila terbukti bersalah, maka pelaku pidana korupsi dan terbukti bersalah dapat dikenai pidana maksimal. Pokok permasalahan yang disajikan penyusun didalam pembahasan tindak pidana korporasi dalam perspektif hukum Islam dan hukum positif adalah: 1) Bagaimana pandangan hukum positif terhadap tindak pidana korupsi? dan apa sangsi terhadap pelaku korupsi dalam hukum positif ? 2) Bagaimana pandangan hukum Islam terhadap tindak pidana korupsi? Dan bagaimana sangsi tindak pidana korupsi dalam hukum islam?. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif komperatif yang bersumber dari berbagai referensi baik kitab-kitab klasik maupun buku-buku yang komperensif sebagai acuan utama, yakni dengan cara menyuguhakan penggambaran mengenai masalah korupsi secara komperatif (perbandingan) menurut versi hukum positif dan hukum Islam.dengan maksud untuk mendapatkan jawaban yang relevan dan kredibel sehingga para pembaca atau pencari ilmu dapat mengambil kesimpulan mengenai masalah korupsi dengan tepat. Dari penjelasan deskripsi mengenai tindak pidana korupsi di atas bisa di ambil kesimpulan bahwa,Tindak pidana ditinjau dari sisi agama islam adalah larangan-larangan syara’ yang diancam oleh Allah dengan hukuman had atau ta’zir. Sedangkan menurut hukum positif tindak pidana adalah perbuatan yang melanggar larangan yang diatur oleh aturan hukum yang diancam dengan sanksi pidana. Perbuatan pidana dalam islam akan mendapatkan sanksi yang setimpal, semisal pembunuhan harus dihukum mati. Sedangkan menurut hukum positif, pelanggar tindak pidana dihukum dengan ketentuan yang kondisional, semisal seseorang yang membunuh dihukum hanya sekian tahun hukuman penjara, yang seharusnya adalah hukuman mati, dengan alasan karena kasihan ataupun melindungi hak asasi.